Creativity: A Driver and Enabler of Social Cohesion - García Alcaraz, Teresa (kult-ur, 2017)
Caracas, a city that has been shaped by decades of spatial, social and political division, struggles daily to overcome its complex legacy. Despite government attempts to combat these severe disparities among the population, urban form combined with constrained social imaginations have resulted in the routine replication and deepening of division in the city. Leaving behind the urban dichotomies normally used to describe contemporary cities, which further exacerbate the idea of difference, ‘in-between spaces’ are identified as areas of encounter among ‘strangers’, capable of engendering new relationships and building citizenship. Creativity, in all its senses, is seen as an excellent mechanism for transforming and reshaping the urban and social fabric in these ‘in-between spaces’, revealing multiple languages that are responsible for generating a change of paradigm in the cities of tomorrow.